Post-harvest Industrial Processes of Almond (Prunus dulcis L. Mill) in Sicily Influence the Nutraceutical Properties of By-Products at Harvest and During Storage - Caltagirone, Chiara; Peano, Cristiana; Sottile, Francesco (Frontiers in Nutrition, 2021)
Almond cultivation in Sicily is experiencing a phase of great interest which is mainly concentrated in the development of specialized orchards, with irrigation and by adopting cultivars with high qualitative and quantitative performances. These are mostly Mediterranean genotypes with high fat content and hard or semi-hard shell, extremely different from the varieties of Californian diffusion. The development of the sector comprises the primary production of almonds but also a series of secondary products which often represent a burden for the company. From these considerations several researches have been developed with the aim of giving a value to these by-products through circular economy paths. One of the by-products widely produced, besides the shell, is the skin which covers the seed and is produced during the peeling phase. It is well-known that tegument is an important component of almond because it contains important bioactive substances (phenols and aromas) which are usually dispersed during peeling. This paper examined three different Italian cultivars widely spread in Sicily, two of Apulian origin, (Genco and Tuono), and one locally cultivated variety (Vinci a tutti). These three cultivars occupy an increasingly large area and are very popular with consumers and industry. The production of secondary products, therefore, evidences significant quantities and the possibility to give them an added value becomes a need for the sector. Therefore, the content of phenols and proanthocyanins in the skin at harvest and during storage was analyzed, adopting two different separation methods, with and without water. During the analysis it was possible to observe the different behavior of the three cultivars due to genetic and industrial factors. Skin separated without using hot water showed a higher total phenolic presence with average increases of about 20%, and with even higher increases, between 28 and 32%, for proanthocyanins. Vinci a tutti evidenced the highest total phenolic content after 8 months of storing while roasting has revealed to be a more effective skin separation approach.